(untitled) (Research, Society and Development, 2020)
It is estimated that there are more than 30 thousand people with type 1 diabetes mellitus (DM1) in Brazil. Among the complications, diabetic retinopathy (DR) is one of the most prevalent, affecting up to 50% of DM1 patients in some populations. This study aims to estimate the prevalence of DR in DM1 or Latent autoimmune diabetes in adults (LADA), in addition to assessing risk factors involved. A cross-sectional study was carried out evaluating 81 patients over 18 years of age and diagnosed with long-term type 1 DM. Demographic, clinical and laboratory aspects were assessed using a structured questionnaire. Ophthalmological examination data were collected from medical records. We observed a 33% prevalence of DR in patients with DM1 in the state of Ceará. This complication was more associated with older patients (p = 0.004), longer DM1 time (p <0.001), inadequate metabolic control and, mainly, increased creatinine levels (p = 0.011). It was observed that patients with episodes of severe hypoglycemia had a higher prevalence of DR. In addition, an important association was observed between DR and diabetic nephropathy, as described in the literature. This study demonstrates the high prevalence of DR in patients with DM1 and confirms the need for tracking the disease, especially in patients with longer disease duration and inadequate metabolic control and other complications such as nephropathy.